Asthma Research and Practice - Braido, Fulvio
Asthma Research and Practice is the official publication of Interasma and publishes cutting edge basic, clinical and translational research in addition to hot topic reviews and debate articles relevant to asthma and related disorders (such as rhinitis, COPD overlapping syndrome, sinusitis). The journal has a specialized section which focusses on pediatric asthma research. Asthma Research and Practice aims to serve as an international platform for the dissemination of research of interest to pulmonologists, allergologists, primary care physicians and family doctors, ENTs and other health care providers interested in asthma, its mechanisms and comorbidities.